2019
DOI: 10.12795/revistafuentes.2018.v21.i1.05
|View full text |Cite
|
Sign up to set email alerts
|

Competencia comunicativa y nuevas tecnologías en el proceso de localización web: modelo MDPT para la formación de profesionales en localización.

Abstract: Accessing external markets has become a priority for companies given the constant changes in the economic environment boosted by globalization. Website localization constitutes a new field of study and professional intervention within the translation field. Localization is the process of adapting a website to the typological, discursive and genre conventions of the target language adapting that website to a different language and culture. Undoubtedly, excellent language skills are essential for the translation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 13 publications
1
3
0
Order By: Relevance
“…Those results point to a close relationship between the industry and university in the specific context of localisation, a field that requires responsiveness to the real world, as insisted on by the translation industry itself (Arevalillo Doval 2020). They also reflect the more recent approaches to localisation training, as mentioned in the previous section (Granell 2011: 188-189;Gutiérrez-Artacho et al 2019;Muegge 2018). The final profile-related question (number 8) aimed to establish how familiar localisation trainers were with different translation tools and software.…”
Section: Localisation Trainer Profiles (Questions 1-8)supporting
confidence: 65%
See 2 more Smart Citations
“…Those results point to a close relationship between the industry and university in the specific context of localisation, a field that requires responsiveness to the real world, as insisted on by the translation industry itself (Arevalillo Doval 2020). They also reflect the more recent approaches to localisation training, as mentioned in the previous section (Granell 2011: 188-189;Gutiérrez-Artacho et al 2019;Muegge 2018). The final profile-related question (number 8) aimed to establish how familiar localisation trainers were with different translation tools and software.…”
Section: Localisation Trainer Profiles (Questions 1-8)supporting
confidence: 65%
“…Another important aspect that has been emphasised recently is collaborating with the industry on real-life projects. Involving other experts and professionals is also called for (Bilali 2018: 189;Granell 2011: 188-189;Gutiérrez-Artacho et al 2019;Muegge 2018), and, if possible, approaching localiser training as collaborative project management (Esqueda 2020;Kudła 2017), situated and embodied learning (Calvo 2015;Risku 2010), emergent expertise (Kiraly 2013;Kenny 2020: 504), or coemergent experiential learning and transdisciplinary action-research (Massey 2021(Massey , 2019.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…They identified and analyzed the game mechanics which are best adapted to the subjects and competences connected with the Translation and Interpreting undergraduate degree program and concluded that the methodology of videogames -rewarding players in order to monitor their progress-would be effective in keeping students fully motivated. In addition, the PATT model was redesigned and adapted in order to integrate all the knowledge and skills required by the new professional profile of web locators [45], [46]. All these innovative methodologies are focused on translation training as a general professional activity.…”
Section: Disruptive Methodologies In Translation and Interpretingmentioning
confidence: 99%